Hazes and clouds in a singular triple vortex in Saturn's atmosphere from HST/WFC3 multispectral imaging - Sanz-Requena, J; Perez-Hoyos, S; Sanchez-Lavega, A; Del Rio-Gaztelurrutia, T; Irwin, P (Elsevier, 2019)
In this paper we present a study of the vertical haze and cloud structure over a triple vortex in Saturn's atmosphere in the planetographic latitude range 55°N-69°N (del Río-Gaztelurrutia et al., 2018) using HST/WFC3 multispectral imaging. The observations were taken during 29–30 June and 1 July 2015 at ten different filters covering spectral range from the 225 nm to 937 nm, including the deep methane band at 889 nm. Absolute reflectivity measurements of this region at all wavelengths and under a number of illumination and observation geometries are fitted with the values produced by a radiative transfer model. Most of the reflectivity variations in this wavelength range can be attributed to changes in the tropospheric haze. The anticyclones are optically thicker (τ ~25 vs ~10), more vertically extended (~3 gas scale heights vs ~2) and their bases are located deeper in the atmosphere (550 mbar vs 500 mbar) than the cyclone.